Diversification, networks and the survival of exporting firms (2011)
There is abundant empirical evidence testing models where comparative advantage arises from firm heterogeneity. As of today it is relatively clear who exports and why a firm decides to export. But, what determines the survival of a firm in the export market? This paper exploits a detailed developing economy monthly firm-level dataset for the period 2001 - 2008 in order to explore the importance of trade networks and product and market diversification on the survival of exporting firms. We find that market diversification prevails over product diversification while trade network effects, measured in various ways, are highly correlated to the survival of new exporting firms. From a policy perspective our findings suggest that government aid in the exporting process should focus on expanding into new markets, not on promoting new export products.